Being a gift- Multilingual healthcare professionals in neonatal care. Issue 1 (February 2022) - Patriksson, Katarina; Nilsson, Stefan; Wigert, Helena
Abstract: Background: Parents said that they sometimes wished they had a multilingual physician as an interpreter, because the physician would understand the child's care and treatment and share a language with the parents. Aim: To understand and describe the lived experience of multilingual neonatal healthcare professionals dealing with interpreting in their workplace, performing as interpreters in addition to their regular work. Methods: Interviews with multilingual neonatal healthcare professionals and analysed using a phenomenological reflective lifeworld approach. Results: Multilingual healthcare professionals understood the interpreting experience as being a gift, comprising three themes: feeling satisfaction – happiness from helping workplace colleagues; identifying with families – empathy from having been in the same situation; and expected to be available – colleagues expected them to provide interpreting services. Conclusion: This study found that it is common in neonatal care to use multilingual healthcare professionals to interpret communication with parents when language barriers exist.